Pengaruh Good Corporate Governance Dan Rasio Keuangan Terhadap Financial Distress (Studi Pada Subsektor Tekstil Dan Garmen Tahun 2016-2019 Di Bursa Efek Indonesia) (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine good corporate governance and financial ratios have an influence or not on financial distress. The population used is the textile and garment sub-sector companies in 2016-2019 which are listed on Bursa Efek Indonesia. The technique in sampling is purposive sampling. The companies included in the study criteria consisted of 12 companies for 4 years. The method of collection in this study is the annual report documentation and literature, namely from journals and articles. The analysis used logistic regression and tested the hypothesis with sig values in the logistical test results table.This study has the results of the board of directors, independent board of commissioners, managerial ownership, institutional ownership, liquidity ratios, leverage ratios, and profitability ratios have no significant effect on financial distress. Keywords: Good Corporate Governance, Board of Directors, Independent Board of Commissioners, Managerial Ownership, Institutional Ownership, Liquidity Ratio, Leverage Ratio, Profitability Ratio and Financial Distress